Interfacial reaction between Sn-rich solders and Ni-based metallization - Kumar, A. (2012)
Solid state reaction between Sn-rich solders (Sn–3.5Ag and Sn–37Pb) and two types of Ni-based metallization (electroless Ni–P and sputtered Ni) has been studied. The growth rates of the main intermetallic compound (IMC), Ni3Sn4, at different aging temperatures are obtained and the activation energy calculated. Ni3Sn4 grows faster with Sn–3.5Ag solder than with Sn–37Pb solder under the same aging condition. The activation energy for the IMC growth with Ni–P metallization is higher than that with sputtered Ni metallization. Kirkendall voids are found inside Ni3P layer after thermal aging in the solder/Ni–P UBM systems. This is the result of unbalanced element diffusion in solid state reaction between Sn-rich solders and Ni–P metallization. No voids are formed in solder/Ni system.